2020
DOI: 10.1111/padm.12642
|View full text |Cite
|
Sign up to set email alerts
|

The role(s) of accounting and performance measurement systems in contemporary public administration

Abstract: The spate of public sector reforms which have taken place in recent decades has triggered the development of a new body of research around public sector accounting and performance measurement both in public administration as well as in the (public sector) accounting literature. However, studies in accounting and public administration have at times ignored each other, proceeding in parallel. This symposium encourages the adoption of interdisciplinary perspectives in exploring the myriad roles played by accounti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 101 publications
7
66
0
2
Order By: Relevance
“…Many countries have adopted neoliberal ideas and reforms based on new public management (NPM) policies and techniques, by imposing "quasi competition" and "business-like" management models in the public sector. NPM is a logic steeped in the management structures of the private business sector (Guthrie et al, 1990) and markets (Steccolini et al, 2020) aimed at reducing the size of the public sector and reasserting political control (Guthrie et al, 1998).…”
Section: Neoliberalism In Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…Many countries have adopted neoliberal ideas and reforms based on new public management (NPM) policies and techniques, by imposing "quasi competition" and "business-like" management models in the public sector. NPM is a logic steeped in the management structures of the private business sector (Guthrie et al, 1990) and markets (Steccolini et al, 2020) aimed at reducing the size of the public sector and reasserting political control (Guthrie et al, 1998).…”
Section: Neoliberalism In Australiamentioning
confidence: 99%
“…Interdisciplinary accounting researchers have provided a sustained critique of the role of accounting within neoliberalism (e.g. Andrew and Cahill, 2017;Zhang and Andrew, 2014), the limitations of market-based solutions (Newberry and Brennan, 2013;Nikidehaghani et al, 2019), and the transformations of public sector accounting that have dominated the last 40 years of reforms (Guthrie and Parker, 2011;Steccolini et al, 2020).…”
Section: Neoliberalism In Australiamentioning
confidence: 99%
“…Last but not least, another set of previous studies have examined this trendy topic from the perspective of the alleged relationship between smart cities, neoliberalism and socio-political urban developments (Tan and Taeihagh, 2020; Raucci and Tarquinio, 2020; Grossi and Pianezzi, 2017; Meijer et al , 2017; Hollands, 2008). However, despite these valuable efforts and attempts to provide different theoretical and empirical perspectives on the potential relationship between performance measurement and smart city governance, these research endeavours have indicated that smart city governance requires complex decisions to be made with attention to economic, social and environmental performance (Tan and Taeihagh, 2020; Raucci and Tarquinio, 2020; Grossi et al , 2020), but with not enough attention to also “political intervention” (Steccolini et al , 2020; Meijer et al , 2017), “military engagement” (Alawattage and Alsaid, 2018; Noguchi et al , 2015) and “public-private collaboration” (Mutiganda et al , 2020; Alsaid and Mutiganda, 2020) in place. Although these angles have been widely theorised in public sector management accounting research, especially in neoliberalism and its various forms of privatisation, modernisation and state budget reforms (see, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This line of research exists at the intersection of two broader academic discourses. One addresses new public management (NPM) and PM (e.g., Hood, 1995;Steccolini et al, 2020); the other studies changes in higher education organizations and the academic profession (e.g., Kallio et al, 2020;Martin-Sardesai et al, 2019). Over the last few decades, numerous studies have identified fundamental changes in academia that are typically connected to underlying assumptions concerning the nature of academia in general and how university organizations are managed in particular.…”
Section: Competing Institutional Logics and Their Effects On Institutional Work In Academiamentioning
confidence: 99%